"No text is innocent": Canadian children's books in the classroom - Joyce Bainbridge; Diane Oberg; Mike Carbonaro (University of Windsor, 2006)
This case study of one school district explored elementary teachers' use of, and beliefs about, Canadian children's books in the classroom. It also examined the supports that facilitate elementary teachers' use of Canadian books, including services provided by teacher-librarians, school district personnel and others; availability of funding; and opportunities for professional development. The case study district had a teacher-librarian in every school and was committed to supporting the work of teachers through the school library. The participants had clear ideas about what it meant to them to be Canadian and about the values that were important to them as Canadians. They believed it was important to incorporate Canadian books into classroom activities. However, they often felt a need to justify their use of Canadian books, whereas they unquestioningly used American books in their teaching across the curriculum. Overall, they were more knowledgeable about Canadian books and Canadian authors and illustrators than teachers in earlier studies. However, the findings of the study raise an interesting paradox; the teachers supported the use of Canadian books but they did not appear to connect "Canadian values" to Canadian books. They seemed unaware that all books, Canadian or not, convey an ideology; "no text is innocent" (Stephens & Watson, 1994, p. 14).